Potential differences in ephedrine requirements between left lateral and right lateral decubitus positions during neuraxial anesthesia for cesarean delivery - Wu, Shanshan (Frontiers in Medicine, 2024)
The recent article by Wen et al., published in PLOS ONE, titled “Effects of neuraxial anesthesia in sitting and lateral positions on maternal hemodynamics in cesarean section: A systematic review and meta-analysis,” caught my attention. In their study, the authors observed the effects of neuraxial anesthesia in sitting and lateral positions on maternal hemodynamics during cesarean section. Given the anatomical differences between the left and right sides of the body, which could result in differences in maternal hemodynamics and vasopressor requirements during neuraxial anesthesia for cesarean delivery, I was intrigued by the idea of further dividing the lateral position data from Wen et al.'s study into three subgroups: “left lateral position,” “right lateral position,” and “not mentioned” (where the included original study did not mention the lateral position) for a subgroup analysis. It seems to be more rigorous, the subgroup analysis revealed that the usage rate of ephedrine support was 1.42 times higher for parturients in the right lateral position compared to those in the sitting position. This finding supports our recommendation to distinguish between left and right lateral decubitus positioning in neuraxial anesthesia for cesarean delivery. But in contrast, no significant difference was observed between the sitting and lateral positions in terms of the number of parturients requiring ephedrine in Wen et al.'s. Given the limited research on the right-lateral position and its hemodynamic effects, further studies are needed to explore its clinical applications. Future research should also focus on conducting larger trials with greater sample sizes to evaluate the long-term neonatal outcomes associated with varying maternal positions. Additionally, researchers should conduct subgroup analyses that separate the left- and right-lateral positions to provide clearer guidance for anesthesiologists.